Pengembangan Model Pembelajaran Lompat Berbasis Discovery Learning Untuk Siswa Kelas 8 SMPN 6 Singosari - Purwanto, Febri Fitra; Mu’arifin, Mu’arifin (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This research aims to design and develop learning media for jumping based on discovery learning for grade 8 students of SMPN 6 Singosari. With this development product, it is hoped that it can be utilized as a reference for independent learning resources for grade 8 students of SMPN 6 Singosari and can spur increased student interest in learning. For this research, the researcher chose to apply a research and development (R&D) approach in accordance with the framework proposed by Lee and Owen. The data analysis methods applied included qualitative and quantitative approaches using a percentage format. Quantitative information was obtained through multiple expert validations and group trials. The percentage from media experts was 98.33%, 93.75% by learning experts, 100% by material experts, 89.5% by small group trials, and 90% by large group trials. From the results of data analysis and discussion that has been presented, then the conclusion is that the product development of a discovery learning-based jump learning model for SMPN 6 Singosari can be said to be feasible to use.